Defining reference conditions for coastal areas in the Baltic Sea - Andrén, Elinor; Clarke, Annemarie; Telford, Richard; Weckström, Kaarina; Vilbaste, Sirje; Aigars, Juris; Conley, Daniel; Johnsen, Torbjørn; Juggins, Steve; Korhola, Atte (TemaNord, 2007)
The overall aim of DEFINE is to provide a methodology to define reference conditions for nutrient concentrations in the coastal zone of the Baltic Sea. This will aid the national authorities that surround the Baltic basin in implementing the EU's Water Framework Directive (WFD) by providing decision-makers with a methodology to assess reference conditions and the degree of past and present departure from this state, such that appropriate policy and management measures can be taken at national and European levels. DEFINE adopts a palaeoecological approach grounded on diatom-based transfer functions, which can then be applied to define background total nitrogen (TN) concentrations in estuaries and coastal areas over the entire Baltic Sea. All transfer functions and necessary supporting documentation will be publicly available as a coherent management tool and accessible via the MOLTEN/DEFINE web page (http://craticula.ncl.ac.uk/Molten/jsp/).